Cover Picture: Inorganic and Organometallic Molecular Wires for Single‐Molecule Devices (Chem. Eur. J. 20/2017). Issue 20 (20th February 2017) - Tanaka, Yuya; Kiguchi, Manabu; Akita, Munetaka
Abstract : Recent advances in molecular wires containing transition metal centers applied to single molecule devices are reviewed. The properties and functions of the inorganic and organometallic molecular wires can be easily tuned by changing the metal centers, just like changing a piece of the jigsaw puzzle depicted in the artwork. More information can be found in the Concept by Y. Tanaka, M. Kiguchi and M. Akita onpage 4741 ff.